The growth of northeastern Tibet and its relevance to large‐scale continental geodynamics: A review of recent studies. Issue 5 (3rd October 2013) - Yuan, Dao‐Yang; Ge, Wei‐Peng; Chen, Zhen‐Wei; Li, Chuan‐You; Wang, Zhi‐Cai; Zhang, Hui‐Ping; Zhang, Pei‐Zhen; Zheng, De‐Wen; Zheng, Wen‐Jun; Craddock, William H.; Dayem, Katherine E.; Duvall, Alison R.; et al.
Abstract [1] Recent studies of the northeastern part of the Tibetan Plateau have called attention to two emerging views of how the Tibetan Plateau has grown. First, deformation in northern Tibet began essentially at the time of collision with India, not 10–20 Myr later as might be expected if the locus of activity migrated northward as India penetrated the rest of Eurasia. Thus, the north‐south dimensions of the Tibetan Plateau were set mainly by differences in lithospheric strength, with strong lithosphere beneath India and the Tarim and Qaidam basins steadily encroaching on one another as the region between them, the present‐day Tibetan Plateau, deformed, and its north‐south dimension became narrower. Second, abundant evidence calls for acceleration of deformation, including the formation of new faults, in northeastern Tibet since ~15 Ma and a less precisely dated change in orientation of crustal shortening since ~20 Ma. This reorientation of crustal shortening and roughly concurrent outward growth of high terrain, which swings from NNE‐SSW in northern Tibet to more NE‐SW and even ENE‐WSW in the easternmost part of northeastern Tibet, are likely to be, in part, a consequence of crustal thickening within the high Tibetan Plateau reaching a limit, and the locus of continued shortening then migrating to the northeastern and eastern flanks. These changes in rates and orientation also could result from removal of some or all mantle lithosphere and increased gravitational potential energy per unit area and from a weakening of crustal material so that it could flow in response to pressure gradients set by evolving differences in elevation.